2006
DOI: 10.1111/j.2042-3306.2006.tb05540.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated exercise and recovery on heart rate variability in elite trotting horses during high intensity interval training

Abstract: HRV can provide breathing frequency data of Standardbreds during training without any respiratory device. Furthermore, HRV could provide useful makers of the emergence of fatigue states during training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…The finding is in agreement with other studies showing that physical effort increases the LF/HF component in exercised horses (Cottin et al . ; Matsuura et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding is in agreement with other studies showing that physical effort increases the LF/HF component in exercised horses (Cottin et al . ; Matsuura et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent studies, the analysis of HRV has been suggested as an appropriate and, furthermore, easy‐to‐use method for the detection of imbalance between ANS function, training and recovery which may result in a decrease of maximal output (Cottin et al . ; Kinnunen et al . ; Matsuura et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moderate exercise of horses decreased HF power and increased LF power (Voss et al, 2002;Cottin et al, 2005) whereas intensive physical exertion led to decreased LF power and increased HF power (Physick-Sheard et al, 2000;Cottin et al, 2005Cottin et al, , 2006. During high speed exercise the breathing frequency is directly related to the stride frequency.…”
Section: Influence Of Physical Exertionmentioning
confidence: 95%
“…During high speed exercise the breathing frequency is directly related to the stride frequency. HF-power in turn is affected by respiratory frequency and thus increases with high speed exercise (gallop) (Physick-Sheard et al, 2000;Cottin et al, 2006). Hence, HRV analysis assessment of autonomous system activity is not suitable for intensive physical exertion and respiratory-gait entrainment (Physick-Sheard et al, 2000).…”
Section: Influence Of Physical Exertionmentioning
confidence: 99%
“…However, the latest studies of Cottin et al (2005Cottin et al ( , 2006 suggested the lack of positive effect of this type of training. Although, it is known that in adult mares the interval exercise test was associated with alterations of plasma leptin and ghrelin levels ).…”
Section: Discussionmentioning
confidence: 99%